Changes in operational risk management in Polish co-operative banks - Garczyński, Dariusz (Publishing House of the Wrocław University of Economics, 2009)
The share of the co-operative bank sector in 2008 in the balance sheet total of the bank sector in Poland amounted to 5.4%, in credit for the nonfinancial sector to 5.4%, in credit for households to 6.8%, in deposits of the non-financial sector to 8.4%, in deposits of households to 11% and in the net result to about 6.5%. A good financial condition of the sector manifests itself in the average solvency ratio of 13.2%, and the participation of credits in danger from the non-financial sector at the level of 2.8%. With reference to the indicator of credits in danger its about 1.5% better than the same indicator of commercial banks. (fragment tekstu)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 59, s. 191-197